Selective removal of tin from industrial waste with ion exchange resins - Hagad, Luciana T. (1979)
Ion exchange, the phenomena of trading one ion for another has been employed in the recovery of metals from industrial waste stream. In this study, an ion exchange process is applied for the selective removal of tin metal from industrial waste occurring in scrap tinplates, plating rinse water and sludge. The essence of the process is the use if Dowex SBR-P, a strongly basic anion exchange resin of the trimethyl ammonium polystyrene type for the selective removal of anionic complex tin ions. The resin is readily regenerated with 10% NaCl solution.
The selective removal of tin ions was investigated as a function of flow rate, pH and concentration of the exhausting solution. It was shown that Dowex SBR-P anion exchange resin exhibits a high capacity at low flow rates and a high feed solution concentration. This type of resins can be used effectively at a pH between 3.6 and 4.5 to recover tin ions. Ion exchange resin was found to be effective in concentrating dilute solutions.
Mimeographed.
Thesis (M.S.)--University of the Philippines Diliman.
Keywords: Ion exchange resin; Ion exchange; Tin